OVIDʼS HIDDEN LAST LETTERS ON HIS EXILE – TELESTICHS FROM TOMIS: POSTCODE OR CODE?. (December 2020) - Mitchell, Keith
Abstract : Ovid is clear that the cause of his exile was a carmen and an error, the one his poem the Ars amatoria (although written several years before his exile in AD 8), the other something which he was never allowed to explain. This paper argues that Ovid has encrypted a plausibly deniable statement contradicting the official reason for his exile in three interrelated telestichs in his Fasti, a work already known to have been revised in exile.